2009
DOI: 10.1155/2009/906013
|View full text |Cite
|
Sign up to set email alerts
|

A New Technique for Simple Renal Cyst: Cystoretroperitoneal Shunt

Abstract: Purpose. To evaluate the results of patient symptoms and radiologic outcomes of cystoretroperitoneal shunt (CRS) technique in the treatment of symptomatic simple renal cysts. Patients and Methods. In a prospective study, 37 patients with a simple renal cyst were treated with ultrasound-guided percutaneous CRS-catheter. Radiological success was indicated as no recurrence of the cyst or a reduction in cyst volume by at least half. Results. CRS technique was performed successfully in 36 patients with a simple ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…13 Laparoscopy is an effective method to manage simple renal cysts, but it is technically difficult, necessitating a long learning curve for the surgeon, expensive, and needs extensive retroperitoneal dissection. 1,14,15 Ureteroscopic marsupialization was first reported in 1991 5 as a complete transurethral natural orifice translumenal endoscopic surgery (NOTES) 16 that was significantly less invasive than percutaneous nephroscopy or laparoscopy. 4,14 Unfortunately, no large case series studies have reported on the success of this technique in the management of simple renal cysts.…”
Section: Introductionmentioning
confidence: 99%
“…13 Laparoscopy is an effective method to manage simple renal cysts, but it is technically difficult, necessitating a long learning curve for the surgeon, expensive, and needs extensive retroperitoneal dissection. 1,14,15 Ureteroscopic marsupialization was first reported in 1991 5 as a complete transurethral natural orifice translumenal endoscopic surgery (NOTES) 16 that was significantly less invasive than percutaneous nephroscopy or laparoscopy. 4,14 Unfortunately, no large case series studies have reported on the success of this technique in the management of simple renal cysts.…”
Section: Introductionmentioning
confidence: 99%